PENGARUH SARANA DAN PRASARANA KAMPUS TERHADAP MOTIVASI DAN PRESTASI AKADEMIK MAHASISWA DI FISIP UNIVERSITAS RIAU - Desmayeti "; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study was conducted at FISIP Universitas Riau. The study is titled Influence of Campus Facilities and Infrastructure on Student Motivation and Achievement at FISIP Universitas Riau. The purpose of this study is to determine the pattern of utilization of campus facilities and infrastructure by students at FISIP Universitas Riau. The focus of this research is the influence of campus facilities and infrastructure on student's academic motivation and achievement at FISIP Universitas Riau. The subjects studied were 100 students at FISIP Universitas Riau. The authors used inferential quantitative methods and data were analyzed quantitatively and using the sampling ramdom sampling technique. Data instruments are observations, questionnaires and documentation. Research conducted at FISIP Universitas Riau about Influence of Campus Facilities and Infrastructure on Student Motivation and Achievement at FISIP Universitas Riau Has been done by generating the conclusion that testing hypothesis, obtained value of regression coefficient in this research is Y = 17,100 + 0,60 X. Constant value (a) equal to 17,100 and coefficient of typical person variable equal to 0,60. Meanwhile t count 5,765 bigger compared to t table 3,374, with significance level 0.000 smaller than α = 0,05. It means that alternative hypothesis is accepted. Based on statistical calculations obtained, Thus it can be concluded that there is influence of Facility and Infrastructure Campus on Student Achievement Motivation and Achievement at FISIP Universitas Riau. Keywords: Motivation, Student, Facilities and Infrastructure